Independent evolution of oleate hydratase clades in Bacillales reflects molecular convergence - Neff, Robert J.; Lages, Priscilla C.; Donworth, Shannon K.; Brien, James D.; Radka, Christopher D. (Frontiers in Molecular Biosciences, 2024)
Oleate hydratase (OhyA), a flavoenzyme that catalyzes the hydration of unsaturated fatty acids, has been identified in various Bacillales organisms, including those in the Listeria, Lysinibacillus, Paenibacillus, and Staphylococcus genera. In this study, we combine structural biology with molecular and phylogenetic analyses to investigate the evolutionary dynamics of the OhyA protein family within the Bacillales order. Our evolutionary analysis reveals two distinct OhyA clades (clade I and clade II) within Bacillales that, while sharing catalytic function, exhibit significant genomic and structural differences. Our findings suggest that these OhyA clades originated from independent evolutionary processes through convergent evolution rather than gene duplication. We also show that the evolutionary divergence in OhyA is likely due to intrinsic sequence variations rather than being strictly linked to functional domain changes. Furthermore, within the Staphylococcus genus, we observed that the evolution of the ohyA gene aligns with the species tree, supporting a common ancestral origin. This study enhances our understanding of the impact of evolutionary history on the structure and function of OhyA across the Bacillales order.